An Analysis of the Decisions Made for Contralateral Prophylactic Mastectomy and Breast Reconstruction. Issue 1 (July 2016) - Buchanan, Patrick J.; Abdulghani, Mariam; Waljee, Jennifer F.; Kozlow, Jeffrey H.; Sabel, Michael S.; Newman, Lisa A.; Chung, Kevin C.; Momoh, Adeyiza O.
Abstract : Background: Little is known about the role breast reconstruction plays in decisions made for contralateral prophylactic mastectomy. This study explores factors critical to patient medical decision-making for contralateral prophylactic mastectomy and reconstruction among women with early stage, unilateral breast cancer. Methods: A mixed methods approach was used to gain an understanding of patients' choices and experiences. Patients with stage 0 to III unilateral breast cancer who underwent reconstruction were recruited, and semistructured interviews were conducted. Patient-reported outcomes were evaluated using the Concerns About Recurrence Scale and the BREAST-Q. Results: Thirty patients were enrolled; 13 (43 percent) underwent unilateral mastectomy and 17 (57 percent) underwent contralateral prophylactic mastectomy. Three broad categories emerged from patient interviews: medical decision-making, quality of life after mastectomy, and breast reconstruction expectations. Patients who chose contralateral prophylactic mastectomy made the decision for mastectomy based primarily on worry about recurrence. Quality of life after mastectomy was characterized by relief of worry, especially in patients who chose contralateral prophylactic mastectomy [ n = 14 (82.4 percent)]. Patients' desires for symmetry, although not the primary reason for contralateral prophylactic mastectomy, played a role in supporting decisions made. Levels of worry after treatment were similar in both groups (72.7 percent). Patients with contralateral prophylactic mastectomy had higher mean scores for satisfaction with breast (82.4 versus 70.6) and satisfaction with outcome (89.9 versus 75.2). Conclusions: The choice for contralateral prophylactic mastectomy is greatly influenced by fear of recurrence, with desires for symmetry playing a secondary role in decisions made. Abstract : Supplemental Digital Content is available in the text.